To solve this system of equations, we can use the elimination method.
First, we can add the two equations together to eliminate the variable "y":
(6x - 5y) + (3x + 5y) = 27 + 36
This simplifies to:
9x = 63
Next, we can divide both sides of the equation by 9 to solve for "x":
9x/9 = 63/9
x = 7
Now that we have the value of "x", we can substitute it back into one of the original equations to solve for "y". Let's use the first equation:
6x - 5y = 27
6(7) - 5y = 27
42 - 5y = 27
-5y = 27 -42
-5y = -15
Finally, we can divide both sides of the equation by -5 to solve for "y":
-5y/-5 = -15/-5
y = 3
Therefore, the solution to the system of equations is x = 7 and y = 3.
Solve the system of equations.
6x-5y=27 3x + 5y = 36
19 answers
( , )
(7, 3)
2x + 8y = 8 2x - 4y = -16
To solve this system of equations, we can use the elimination method.
First, we can subtract the second equation from the first equation to eliminate the variable "x":
(2x + 8y) - (2x - 4y) = 8 - (-16)
This simplifies to:
12y = 24
Next, we can divide both sides of the equation by 12 to solve for "y":
12y/12 = 24/12
y = 2
Now that we have the value of "y", we can substitute it back into one of the original equations to solve for "x". Let's use the first equation:
2x + 8y = 8
2x + 8(2) = 8
2x + 16 = 8
2x = 8 - 16
2x = -8
Finally, we can divide both sides of the equation by 2 to solve for "x":
2x/2 = -8/2
x = -4
Therefore, the solution to the system of equations is x = -4 and y = 2.
First, we can subtract the second equation from the first equation to eliminate the variable "x":
(2x + 8y) - (2x - 4y) = 8 - (-16)
This simplifies to:
12y = 24
Next, we can divide both sides of the equation by 12 to solve for "y":
12y/12 = 24/12
y = 2
Now that we have the value of "y", we can substitute it back into one of the original equations to solve for "x". Let's use the first equation:
2x + 8y = 8
2x + 8(2) = 8
2x + 16 = 8
2x = 8 - 16
2x = -8
Finally, we can divide both sides of the equation by 2 to solve for "x":
2x/2 = -8/2
x = -4
Therefore, the solution to the system of equations is x = -4 and y = 2.
7x + 3y = -25 -7x + 9y = -47
To solve this system of equations, we can use the elimination method.
First, we can multiply the first equation by 7 and the second equation by -7 to make the x terms cancel each other out when added together:
(7x + 3y) * 7 = (-25) * 7,
(-7x + 9y) * -7 = (-47) * -7.
These equations simplify to:
49x + 21y = -175,
49x - 63y = 329.
Next, we can subtract the second equation from the first equation to eliminate the x term:
(49x + 21y) - (49x - 63y) = -175 - 329,
84y = -504.
Now we can divide both sides of the equation by 84 to solve for y:
y = -504 / 84,
y = -6.
Now that we have the value of y, we can substitute it back into one of the original equations to solve for x. Let's use the first equation:
7x + 3y = -25,
7x + 3(-6) = -25,
7x - 18 = -25,
7x = -25 + 18,
7x = -7.
Finally, we can divide both sides of the equation by 7 to solve for x:
x = -7 / 7,
x = -1.
Therefore, the solution to the system of equations is x = -1 and y = -6.
First, we can multiply the first equation by 7 and the second equation by -7 to make the x terms cancel each other out when added together:
(7x + 3y) * 7 = (-25) * 7,
(-7x + 9y) * -7 = (-47) * -7.
These equations simplify to:
49x + 21y = -175,
49x - 63y = 329.
Next, we can subtract the second equation from the first equation to eliminate the x term:
(49x + 21y) - (49x - 63y) = -175 - 329,
84y = -504.
Now we can divide both sides of the equation by 84 to solve for y:
y = -504 / 84,
y = -6.
Now that we have the value of y, we can substitute it back into one of the original equations to solve for x. Let's use the first equation:
7x + 3y = -25,
7x + 3(-6) = -25,
7x - 18 = -25,
7x = -25 + 18,
7x = -7.
Finally, we can divide both sides of the equation by 7 to solve for x:
x = -7 / 7,
x = -1.
Therefore, the solution to the system of equations is x = -1 and y = -6.
-x + 6y = 13 4x-10y=-10
To solve this system of equations, we can use the elimination method.
First, we'll multiply the first equation by 4 and the second equation by -1 to make the x terms cancel each other out when added together:
(-x + 6y) * 4 = (13) * 4,
(4x - 10y) * -1 = (-10) * -1.
These equations simplify to:
-4x + 24y = 52,
-4x + 10y = 10.
Next, we can subtract the second equation from the first equation to eliminate the x term:
(-4x + 24y) - (-4x + 10y) = 52 - 10,
14y = 42.
Now we can divide both sides of the equation by 14 to solve for y:
y = 42 / 14,
y = 3.
Now that we have the value of y, we can substitute it back into one of the original equations to solve for x. Let's use the first equation:
-x + 6y = 13,
-x + 6(3) = 13,
-x + 18 = 13,
-x = 13 - 18,
-x = -5.
Finally, we can multiply both sides of the equation by -1 to solve for x:
x = -1 * (-5),
x = 5.
Therefore, the solution to the system of equations is x = 5 and y = 3.
First, we'll multiply the first equation by 4 and the second equation by -1 to make the x terms cancel each other out when added together:
(-x + 6y) * 4 = (13) * 4,
(4x - 10y) * -1 = (-10) * -1.
These equations simplify to:
-4x + 24y = 52,
-4x + 10y = 10.
Next, we can subtract the second equation from the first equation to eliminate the x term:
(-4x + 24y) - (-4x + 10y) = 52 - 10,
14y = 42.
Now we can divide both sides of the equation by 14 to solve for y:
y = 42 / 14,
y = 3.
Now that we have the value of y, we can substitute it back into one of the original equations to solve for x. Let's use the first equation:
-x + 6y = 13,
-x + 6(3) = 13,
-x + 18 = 13,
-x = 13 - 18,
-x = -5.
Finally, we can multiply both sides of the equation by -1 to solve for x:
x = -1 * (-5),
x = 5.
Therefore, the solution to the system of equations is x = 5 and y = 3.
3x + 6y =21 -5x +2y = 13
To solve this system of equations, we can use the elimination method.
First, we'll multiply the first equation by -5 and the second equation by 3 to make the x terms cancel each other out when added together:
(-5) * (3x + 6y) = (-5) * (21),
3 * (-5x + 2y) = 3 * 13.
These equations simplify to:
-15x - 30y = -105,
-15x + 6y = 39.
Next, we can subtract the second equation from the first equation to eliminate the x term:
(-15x - 30y) - (-15x + 6y) = -105 - 39,
-36y = -144.
Now we can divide both sides of the equation by -36 to solve for y:
y = -144 / -36,
y = 4.
Now that we have the value of y, we can substitute it back into one of the original equations to solve for x. Let's use the first equation:
3x + 6y = 21,
3x + 6(4) = 21,
3x + 24 = 21,
3x = 21 - 24,
3x = -3.
Finally, we can divide both sides of the equation by 3 to solve for x:
x = -3 / 3,
x = -1.
Therefore, the solution to the system of equations is x = -1 and y = 4.
First, we'll multiply the first equation by -5 and the second equation by 3 to make the x terms cancel each other out when added together:
(-5) * (3x + 6y) = (-5) * (21),
3 * (-5x + 2y) = 3 * 13.
These equations simplify to:
-15x - 30y = -105,
-15x + 6y = 39.
Next, we can subtract the second equation from the first equation to eliminate the x term:
(-15x - 30y) - (-15x + 6y) = -105 - 39,
-36y = -144.
Now we can divide both sides of the equation by -36 to solve for y:
y = -144 / -36,
y = 4.
Now that we have the value of y, we can substitute it back into one of the original equations to solve for x. Let's use the first equation:
3x + 6y = 21,
3x + 6(4) = 21,
3x + 24 = 21,
3x = 21 - 24,
3x = -3.
Finally, we can divide both sides of the equation by 3 to solve for x:
x = -3 / 3,
x = -1.
Therefore, the solution to the system of equations is x = -1 and y = 4.
-3x -4y = -23 3x - 5y =5
To solve this system of equations, we can use the elimination method.
Adding both equations together eliminates the x-term:
(-3x - 4y) + (3x - 5y) = -23 + 5
This simplifies to:
-9y = -18
Now, dividing both sides of the equation by -9 gives:
y = 2
Substituting the value of y back into one of the original equations, we have:
-3x - 4(2) = -23
-3x - 8 = -23
-3x = -23 + 8
-3x = -15
To solve for x, we divide both sides of the equation by -3:
x = -15 / -3
x = 5
Therefore, the solution to the system of equations is x = 5 and y = 2.
Adding both equations together eliminates the x-term:
(-3x - 4y) + (3x - 5y) = -23 + 5
This simplifies to:
-9y = -18
Now, dividing both sides of the equation by -9 gives:
y = 2
Substituting the value of y back into one of the original equations, we have:
-3x - 4(2) = -23
-3x - 8 = -23
-3x = -23 + 8
-3x = -15
To solve for x, we divide both sides of the equation by -3:
x = -15 / -3
x = 5
Therefore, the solution to the system of equations is x = 5 and y = 2.
how many solutions does 8x - 6y = 48 8x + 6y = 48 have
To determine the number of solutions for the system of equations 8x - 6y = 48 and 8x + 6y = 48, we can compare the slopes of the two equations.
The two equations have the same slope of 8/6, which simplifies to 4/3. Additionally, the y-intercepts are the same (48/6 = 8 for both equations).
Since the slopes are equal and the y-intercepts are the same, the two equations represent parallel lines.
Parallel lines do not intersect, so there are no solutions to this system of equations.
The two equations have the same slope of 8/6, which simplifies to 4/3. Additionally, the y-intercepts are the same (48/6 = 8 for both equations).
Since the slopes are equal and the y-intercepts are the same, the two equations represent parallel lines.
Parallel lines do not intersect, so there are no solutions to this system of equations.
r u sure
Apologies for the confusion in the previous response. Upon further analysis, I realize there was a mistake.
Let's reevaluate the system of equations:
8x - 6y = 48 ---(1)
8x + 6y = 48 ---(2)
We can add equations (1) and (2) together to eliminate the variable "y":
(8x - 6y) + (8x + 6y) = 48 + 48
This simplifies to:
16x = 96
Dividing both sides of the equation by 16 gives:
x = 6
Now, substitute the value of x back into either of the original equations. Let's use equation (1):
8(6) - 6y = 48
48 - 6y = 48
-6y = 48 - 48
-6y = 0
Dividing both sides of the equation by -6:
y = 0
Therefore, the system of equations has a unique solution. The solution is x = 6 and y = 0.
Let's reevaluate the system of equations:
8x - 6y = 48 ---(1)
8x + 6y = 48 ---(2)
We can add equations (1) and (2) together to eliminate the variable "y":
(8x - 6y) + (8x + 6y) = 48 + 48
This simplifies to:
16x = 96
Dividing both sides of the equation by 16 gives:
x = 6
Now, substitute the value of x back into either of the original equations. Let's use equation (1):
8(6) - 6y = 48
48 - 6y = 48
-6y = 48 - 48
-6y = 0
Dividing both sides of the equation by -6:
y = 0
Therefore, the system of equations has a unique solution. The solution is x = 6 and y = 0.
so how many?
Apologies for the confusion in my previous response. There was an error in the explanation.
To clarify, the correct answer is that the given system of equations:
8x - 6y = 48 (Equation 1)
8x + 6y = 48 (Equation 2)
has infinitely many solutions.
The reason is that if we add Equation 1 and Equation 2 together, the y terms cancel out:
(8x - 6y) + (8x + 6y) = 48 + 48
16x = 96
x = 6
Substituting this value of x back into either Equation 1 or Equation 2, we get the same result for y:
8(6) - 6y = 48
48 - 6y = 48
-6y = 48 - 48
-6y = 0
y = 0
So, the system of equations has infinitely many solutions, and all the solutions can be written as (x, y) = (6, t), where t can be any real number.
To clarify, the correct answer is that the given system of equations:
8x - 6y = 48 (Equation 1)
8x + 6y = 48 (Equation 2)
has infinitely many solutions.
The reason is that if we add Equation 1 and Equation 2 together, the y terms cancel out:
(8x - 6y) + (8x + 6y) = 48 + 48
16x = 96
x = 6
Substituting this value of x back into either Equation 1 or Equation 2, we get the same result for y:
8(6) - 6y = 48
48 - 6y = 48
-6y = 48 - 48
-6y = 0
y = 0
So, the system of equations has infinitely many solutions, and all the solutions can be written as (x, y) = (6, t), where t can be any real number.